Factors Influencing Entrepreneurs Business Performance in Small and Medium Businesses: Comparative Analysis Between Demographic and Environmental Factors in Bangladesh (Journal of Business and Technology (Dhaka), 2016)
Performance is viewed as the implementation of an action or ones ability. Good performance is also related with achieving greater market share earning more profit. The main aim of this study is to examine and compare the factors influencing entrepreneurs businesses performance. It is a comparative analysis between the demographic and environment related factors. The present article is a survey-based research. A total number of 400 questionnaires were distributed among some small and medium entrepreneurs. Data on their performance, aspects related to (the respondents) demographic and environment were collected. The data have been analyzed by using SPSS software. A model has been developed in order to show and test the relationship among demographic factors and environment related factors and the entrepreneurs business performance in this study. The results revealed that individually (among entrepreneurs) there is a positive and strong significant influence of position in birth order, number of employees(demographic factors); sources of loan collection and family support(environment-related factors) on entrepreneurs business performance.Journal of Business and Technology (Dhaka) Vol.10(2) 2015; 1-17